Synagogen in Göttingen - Aufbrüche und Abbrüche jüdischen Lebens - Schaller, Berndt (Universitätsverlag Göttingen, 2017)
The book "Synagogues in Göttingen: departures and ceasing of Jewish life," deals with the 700-year history of Jewish life in Göttingen and the various synagogues that have been existing since the beginning of the 14th Century. This is the 2nd, revised and expanded edition.